1982
DOI: 10.1227/00006123-198210000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Supraorbital Approach: Technical Note

Abstract: We describe a modification of an old frontal craniotomy technique which allows excellent access to the floor of the frontal fossa and the superior orbit with less brain retraction than conventional techniques. The procedure is described and suggestions are made for its use. We consider it to be the approach of choice for orbital tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
95
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(98 citation statements)
references
References 0 publications
0
95
0
3
Order By: Relevance
“…In 1918, he and Heuer performed the first pterional or frontolateral approach to the optic chiasm and pituitary gland. 6 Jane, et al, 7 first described the supraorbital approach for aneurysms, orbital tumors, and suprasellar lesions. Delashaw, et al, 4 modified it by incorporating the temporal bone, zygoma, and lateral wall of the orbit within the craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1918, he and Heuer performed the first pterional or frontolateral approach to the optic chiasm and pituitary gland. 6 Jane, et al, 7 first described the supraorbital approach for aneurysms, orbital tumors, and suprasellar lesions. Delashaw, et al, 4 modified it by incorporating the temporal bone, zygoma, and lateral wall of the orbit within the craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Steiger et al 15 and Beseoglu et al 2 incorporated an additional orbital osteotomy to improve surgical freedom. Jane et al 8 reported on the supraorbital approach with an orbital osteotomy to treat the frontal base and parasellar lesions in 1982, and this approach was modified by Delashaw et al 5 by fracturing the orbital roof. Al-Mefty 1 described the supraorbitalpterional approach to cranial base lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Our craniotomy does not extend beyond the supraorbital foramen/notch and provides an adequate surgical corridor without limiting the angle of vision when performed using spinal drainage and sharp dissection of the arachnoid. This provides a wide surgical field because gravity contributes to the retraction of the frontal lobe away from the floor of the anterior fossa on account of head positioning and, compared with a standard frontal approach, the surgeon's line of vision is lowered 1.5 to 2 cm by removal of the lateral supraorbital rim, 6 supraorbital foramen/notch also has the drawback of always involving exposure of the frontal sinus, which occurs less frequently when our approach is selected.…”
Section: Discussionmentioning
confidence: 99%